2015
DOI: 10.1016/j.acha.2014.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Continuous wavelet transforms on n-dimensional spheres

Abstract: In this paper, we are concerned with n-dimensional spherical wavelets derived from the theory of approximate identities. For nonzonal bilinear wavelets introduced by Ebert et al. in 2009 we prove isometry and Euclidean limit property. Further, we develop a theory of linear wavelets. In the end, we discuss the relationship to other wavelet constructions.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(54 citation statements)
references
References 33 publications
1
53
0
Order By: Relevance
“…This concept -generalized to the n-dimensional case -was also studied by the author of the present paper. I showed in [19] that directional derivatives of some zonal wavelets satisfy a slightly modified definition of wavelets derived from approximate identities (see [11,10,9,1,8,3,2] for the origins of this concept and [18] for a comprehensive survey). In [20] I proposed further relaxation on the constraints on wavelets derived from approximate identities and showed that directional derivatives of a wide class of functions are wavelets according to the new definition.…”
Section: Example: Directional Waveletsmentioning
confidence: 99%
“…This concept -generalized to the n-dimensional case -was also studied by the author of the present paper. I showed in [19] that directional derivatives of some zonal wavelets satisfy a slightly modified definition of wavelets derived from approximate identities (see [11,10,9,1,8,3,2] for the origins of this concept and [18] for a comprehensive survey). In [20] I proposed further relaxation on the constraints on wavelets derived from approximate identities and showed that directional derivatives of a wide class of functions are wavelets according to the new definition.…”
Section: Example: Directional Waveletsmentioning
confidence: 99%
“…This section is devoted to the bilinear wavelet transform as defined in [19,Section 3]. The goal is to relax the constraints on a function family to be a wavelet, more precisely, to abandon the condition…”
Section: The Wavelet Transformmentioning
confidence: 99%
“…[1,2,3,4,5,6,7,8,9,11,12,13,14,15,17,18,19,20,22]. I have shown in [19,Section 5] that there are only two essentially different continuous wavelet transforms for spherical signals, namely that based on group theory [2,3] and that derived from approximate identities [10,7,19]. In both cases, square integrable signals are considered, and the inverse transform is performed by an integral that converges in L 2 -norm.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations